O-028 Post-surgical prophylactic embolization of chronic sub-dural hematomas in patients with high recurrence risk: a monocentric study. (22nd July 2019) - Shotar, E; Mathon, B; Lenck, S; Meyblum, L; Degos, V; Premat, K; Sourour, N; Boch, A; Carpentier, A; Clarençon, F
Abstract : Background and purpose: The gold standard treatment for chronic subdural hematomas (cSDHs) is the surgical evacuation through a burr hole. Recurrence after such surgical procedure may occur in 10 to 20% of the cases. Embolization through the middle meningeal artery (MMA) is a promising technique for the treatment of cSDHs. The purpose of our study was to evaluate the feasibility, safety and effectiveness, in terms of recurrence reduction, of post-surgical embolization of cSDH in patients with a high risk of recurrence. Materials and methods: Monocentric retrospective study performed on prospectively collected data at the Pitié-Salpêtrière Hospital. From March 2018 to February 2019, embolizations with calibrated microparticles through the MMA were performed in patients surgically treated for a cSDH with a high risk of recurrence, defined as follows: 1) previous recurrence of cSDH or 2) antiplatelet therapy or 3) full anticoagulation therapy or 4) coagulation disorder or 5) hepathopathy or 6) chronic ethylism. In all patients, a pre-embolization supra-aortic trunks (SATs) CT-angiography was performed to rule out a dumb-bell thrombus on the aortic arch or severe atheroma/tortuosity of the SATs. Results: Forty-four patients met the inclusion criteria during the inclusion period. Two patients were excluded (one in a prolonged comatose state and another with a chronic renal failure). Two patients refused the embolization procedure. A last patient was excluded due to major atheroma on the SATs. Finally, 39 patients with 43 cSDHs (4 patients had bilateral SDHs) underwent the embolization procedure. Thirty-seven embolization procedures (95%) were performed under local anesthesia. Among the 43 cSDHs, 5 (9%) could not be embolized due to catheterization failure (4 cases) or to the presence of a 'dangerous anastomosis' (1 case). No complication (either major or minor) was recorded. Only one recurrence (2.6%) requiring a surgical retreatment was recorded during the follow-up period. Conclusion: Post-surgical embolization through the MMA is a simple and safe procedure, which may reduce the recurrence risk of cSDHs. These preliminary results should be confirmed by randomized controlled trials. Disclosures: E. Shotar: None. B. Mathon: None. S. Lenck: None. L. Meyblum: None. V. Degos: None. K. Premat: None. N. Sourour: 2; C; Medtronic. A. Boch: None. A. Carpentier: None. F. Clarençon: 2; C; Balt, Artedrone, Penumbra.